Gonadotropin and tumorigenesis: Direct and indirect effects on inflammatory and immunosuppressive mediators and invasion. Issue 2 (17th May 2016) - Khare, Priyanka; Bose, Anjali; Singh, Poonam; Singh, Sandhya; Javed, Saleem; Jain, Swatantra Kumar; Singh, Om; Pal, Rahul
Abstract : Human chorionic gonadotropin (hCG), a hormone essential for pregnancy, is also ectopically expressed by a variety of cancers and is associated with poor prognosis; molecular mechanisms which may contribute to tumor progression remain ill‐defined. Exogenous hCG enhanced the viability of human colorectal and lung cancer cells and promoted the growth of syngeneic tumors in mice. It induced the synthesis of VEGF, IL‐8, matrix metalloprotease (MMP)‐2 and MMP‐9, and increased invasiveness in an MMP‐dependent manner. While inducing the secretion of the tumor‐associated extra‐cellular matrix proteoglycan versican from tumor cells, hCG consequently caused the TLR‐2‐mediated generation of the inflammatory, tumor‐associated cytokines TNF‐α and IL‐6 from peripheral blood adherent cells. The molecule up‐modulated the Treg‐associated transcription factor FOXP3 in tumor cells and increased the secretion of TGFβ and IL‐10, thereby inhibiting T cell proliferation and inducing the differentiation FOXP3 ‐ CD4 + CD25 ‐ cells into functional FOXP3 + CD4 + CD25 + suppressor cells. Co‐culture of hCG‐treated tumor cells with mature bone‐marrow derived dendritic cells induced the generation of active indoleamine deoxygenase. While anti‐hCG antibodies restricted the growth of implanted tumor cells in nude mice, immunization of immune competent mice with a βhCG‐TT conjugate supplemented with Mycobacterium indicus pranii provided synergistic survival benefit in animals implanted with syngeneic, hCG‐responsive tumor cells. These studies elucidate the pathways by which hCG can promote tumorigenesis, providing further rationale for anti‐hCG vaccination in the treatment of gonadotropin‐sensitive tumors. © 2016 Wiley Periodicals, Inc.